Annual Report 2019-2020 - Community Health and Social Services Network (CHSSN) (2020)

Rapport annual 2019-2020 - Community Health and Social Services Network (CHSSN) (2020)

2019-2020 Annual Report : Saint Brigid's Home Residents' Committee - Leger, Valerie (Jeffery Hale - Saint Brigids (JHSB), 2020)
The roles and responsibilities of our Residents’ Committee (shared with the Users’ Committee) are to: 1. Inform users of their rights and obligations. 2. Help improve the quality of living conditions and evaluate the degree of satisfaction with the services at the institution. 3. Defend the collective rights and interests of users or, upon request, the rights and interests of an individual user, before the institution or any competent authority. The SBH Residents’ Committee is overseen by the JHSB Users’ Committee. As president, I therefore attended its meetings to receive and give information of interest to SBH. As committees we strive to work closely with administrators at SBH to ensure our concerns translate into quality services for residents.

Rapport du Comité des résidents du Jeffery Hale : Année 2019-2020 - Cloutier, Robert (Jeffery Hale - Saint Brigid's (JHSB), 2020)
Au cours de l’année 2019-2020, le Comité des résidents du Jeff s’est rencontré à sept reprises. Les rencontres se sont tenues principalement au 2e étage du Jeff le troisième vendredi du mois. Étant donné la venue du Coronavirus le Comité a tenu sa dernière séance le 21 février 2020. Par ailleurs, des communications téléphoniques et par courriel ont lieu régulièrement avec les membres. Le Comité est composé de résidents, de proches aidants et d’ex proches aidants. Pour que tous les membres s’impliquent dans les travaux du Comité et que les séances de travail soient plus productiv

[Jeffery Hale - Saint Brigid’s Users’ Committee Annual Report : 2019-2020] - Robertson, Mary (Jeffery Hale - Saint Brigids (JHSB), 2020)
The Jeffery Hale – Saint Brigid’s Users’ Committee met nine times from April 2019 to February 2020 in addition to its Annual Meeting on May 8, 2019. The Annual Meeting was held in conjunction with an Information Meeting by the Administration for Saint Brigid’s Residents and families and was well attended. The March 2020 meeting was cancelled because of the Covid19 virus pandemic. Throughout the year the Committee’s meetings were held in the Saint Brigid’s Boardroom because of renovations to the Jeffery Hale Pavilion.

Annual Report : April 1, 2019 to March 31, 2020 - Quebec English-speaking Communities Research Network (QUESCREN) (2020)

Rapport annuel : période du 1er avril 2019 au 31 mars 2020 - Quebec English-speaking Communities Research Network (QUESCREN) (2020)

Impact Report 2019-2020 - 4Korners (2020)

Rapport d'impact 2019-2020 - 4Korners (2020)

Annual Report 2019-2020 - Committee for Anglophone Social Action (CASA) (2020)

Annual Report 2020-2021 - Community Health and Social Services Network (CHSSN) (2020)

Fondation des Amis du Jeffery Hale – Saint Brigid’s rapport annuel 2019-2020 - Fondation des Amis du Jeffery Hale – Saint Brigid’s (Jeffery Hale - Saint Brigid's (JHSB), 2020)
La mission de la Fondation des Amis consiste à organiser des collectes de fonds pour venir en aide à l’Hôpital Jeffery Hale – Saint Brigid’s dans son objectif d’offrir des services de qualité en santé et services sociaux à tous ses résidents et clientèles. Ce rapport présente les résultats de financement des projets pour l’année 2019.

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)
The Association was founded in November 1962, shortly after Jamaica’s Independence in August 1962. Our seal of Incorporation was granted in 1970. Since its inception, the Association has grown strong in attracting members. It is recognized as the official organization representing Jamaicans in Montreal at the Federal, Provincial and Municipal levels. We are a member of the United Council for Human Rights and have accompanied delegations and presented briefs to all levels of government. Given our commitment to community development, the Jamaica Association developed our Mission Statement as follows: “To assist in improving and enhancing the quality of life for the Jamaican Community”.

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)

[Jeffery Hale - Saint Brigid's Friends' Foundation Annual report 2019-2020] - Jeffery Hale – Saint Brigid’s Friends’ Foundation (Jeffery Hale - Saint Brigid’s (JHSB), 2020)

Jeffery Hale-Saint Brigid's Friends' Foundation Annual Report 2019-2020 - Jeffery Hale – Saint Brigid’s Friends’ Foundation (Jeffery Hale - Saint Brigid's (JHSB), 2020)
The mission of the Friends' Foundation is to raise money to support Jeffery Hale - Saint Brigid's in its quest to provide quality health and social services to all its residents and clients. This report presents the results of the Friends’ Foundation’s projects financed for the year 2019.

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

Annual Report 2019/2020 : 40th Anniversary Edition - Literacy Quebec (LQ) (Literacy Quebec, 2020)

Annual Report : 2019-2020 - Megantic English-speaking Community Development Corporation (MCDC) (2020)

Annual Report : 2019-2020 - NDG Community Council (NDGCC) (2020)

Rapport annuel : 2019-2020 - NDG Community Council (NDGCC) (2020)

Annual Report : 2019-2020 - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)

Rapport Annuel : 2019-2020 - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)

2019-2020 Annual Report - The English Speaking Catholic Council (ESCC) (2020)

Annual Report - Vision Gaspé-Percé Now (2020)